Hunt, Byron, and The Story of Rimini - A Literary Challenge to “the Public Mind” - Bowers, Will (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2011)
This article situates the genesis of second generation Romanticism around the writing, publication, and reception, of Leigh Hunt's The Story of Rimini. It will focus on the period 1814-1816, to find the first expressions of the experimentation which characterise this group. This development has been analysed in Jeffrey Cox's influential Hunt-centred work. Taking a later chronology for his study, Cox claims that these writers were “questing for a position beyond the hegemony of the official culture”. This article disagrees with Cox's positioning of these poets, their works, and “hegemony” (Cox 12). I do not view the poetical works questing for a position “beyond the hegemony”, because of the separation from “official culture” which this articulates. I instead believe that in 1814-1816 Hunt and Byron were constructing poems to confront official culture. Byron's neglected Parisina was written at the same time as Rimini, and I believe that this work was influenced by Hunt. It is a relationship about which criticism is conspicuously silent, preferring instead the “Turkish” tales and Childe Harold. This influence provides a reason for Byron's move from the successful tales, to the more formally and thematically radical work of his exile. There will then be a close-reading of both poems’ experiments in genre (the metrical romance) and form (the heroic couplet). The aim is to view Hunt's poem as a confrontation with two established, and establishment, literary modes while appreciating the social repercussions of such a move. The final section will analyse the organs of “public opinion”, by studying the works’ reception in conservative periodicals. The aim of this analysis will be to challenge critical praxis and appreciate the texts, rather than just their authors' politics, as a threat to the newly formed “public mind”.